INVENTORY THE CHARACTERISTICS OF THE RIVER VETERAN BANJARMASIN CITY FROM TEMPEKONG (STA 0+000) UNTIL THE MARKET KURIPAN(STA 1+219) - Al-Harisnor Al-Harisnor; Maya Amalia; M. Azhari Noor (Universitas Lambung Mangkurat, 2019)
The river in Banjarmasin many experienced dilation and motorsport disappeared. The lack of awareness of the role of the river resulting in the reduction of the capacity of the river tampungan caused by seascape has changed from lagoon Lagoon and a narrowing of the body of the river due to the waste and the building that protrudes to the body of the river. P enelitian done on the city of Banjarmasin, Banjarmasin Sub-East , Jl. The Veteran with a starting point on the river estuary Veteran near the statue of primates/apes to kuripan market . The research method used is to observe call the river Veteran internally obtained characteristics of the river, both in the form of cross channels, channel rainbird capacity , debit cards of the river, by flow pattern and the problems faced by the river Veteran . Results of research has been done, obtained geometric order cross the river, namely the total length of the river 1,219 km(from a starting point of chaired to simpang market Kuripan), the stripe of the river ranges between 4-30 hill and the depth of the river between 0.4 -3 hill, tilt the average basis of the river is of 0,00096, and with the capacity to cross the river between 0,347 -33,916 m3 /s. With Dendritik flow pattern and the problems of the river Veteran is dilation and seascape has changed from lagoon Lagoon due to the waste and the building that protrudes gushed over the river Veteran . Key Words : The River Veteran, Flow pattern, characteristics of the river.